Gram staining of gallbladder bile samples is useful for predicting surgical site infection in acute cholecystitis patients undergoing an early cholecystectomy. (13th July 2020) - Nishida, Yasunori; Otagiri, Noriaki; Yoshifuku, Seijiro; Misawa, Kenji; Ko, Kenju; Sasahara, Kotaro; Mishima, Osamu; Tauchi, Katsunori
Abstract: Background: Microbiological assessment of gallbladder bile is important for postoperative management in cholecystectomy for acute cholecystitis (AC). Gram staining is used as the first step in the assessment, in order to preliminarily detect bacteria in the bile sample. This study was conducted to evaluate the clinical significance of Gram staining results in the development of postoperative surgical site infection (SSI) in AC patients. Methods: A total of 428 AC patients, who underwent an early cholecystectomy with microbiological assessment of gallbladder bile, were enrolled in this retrospective study. The clinical usefulness of the Gram staining results was evaluated by univariate and multivariate regression analyses. Results: Of the 428 patients, 298 patients (69.6%) were diagnosed with bile infection by the Gram staining method. The rate of SSI was higher in patients with bile infection (9.7%) than in those without the infection (0.8%). The multivariate analysis indicated that the bile infection diagnosed by Gram staining (odds ratio: 9.091; P = .033) was an independent factor to predict SSI development, along with open surgery. Conclusions: Gram staining diagnosis of bile infection in an early cholecystectomy for AC is useful for predicting postoperative SSI development, which should benefit postoperative management. Abstract : Nishida and colleagues evaluated the clinical significance of Gram staining results of gallbladder bile in the development of surgical site infection in acute cholecystitis patients. Bile infection diagnosed by Gram staining was an independent factor to predict surgical site infection, which should benefit postoperative management of early cholecystectomy for acute cholecystitis.